National Health Insurance Fund's relationship to retail drug outlets: a Tanzania case study - Martha Embrey; Romuald Mbwasi; Elizabeth Shekalaghe; Jafary Liana; Suleiman Kimatta; Gasto Ignace; Angel Dillip; Tamara Hafner (Taylor & Francis Group, 2021)
Background Achieving universal health coverage will require robust private sector engagement; however, as many low- and middle-income countries launch prepayment schemes to achieve universal health coverage, few are covering products from retail drug outlets (pharmacies and drug shops). This case study aims to characterize barriers and facilitators related to incorporating retail drug outlets into national prepayment schemes based on the experience of the Tanzanian National Health Insurance Fund's (NHIF) certification of pharmacies and accredited drug dispensing outlets. Methods We reviewed government documents and interviewed 26 key informants including retail outlet owners and dispensers and central and district government authorities representing eight districts overall. Topics included awareness of NHIF in the community, access to medicines, claims processing, reimbursement prices, and how the NHIF/retail outlet linkage could be improved. Results Important enablers for NHIF/retail outlet engagement include widespread awareness of NHIF in the community, NHIF's straightforward certification process, and their reimbursement speed. All of the retail respondents felt that NHIF helps their business and their clients to some degree. As for barriers, retailers thought that NHIF needed to provide more information to them and to its members, particularly regarding coverage changes. Some retailers and government officials thought that the product reimbursement prices were below market and not adjusted often enough, and pharmacy respondents were unhappy about claim rejections for what they felt were insignificant issues. All interviewees agreed that one of the biggest problems is poor prescribing practices in public health facilities. They reiterated that prescribers need more supervision to improve their practices, particularly to ensure adherence to standard treatment guidelines, which NHIF requires for approving a claim. In addition, if a prescription has any problem, including a wrong date or no signature, the client must return to the health facility to get it corrected or pay out-of-pocket, which is burdensome. Conclusions Little published information is available on the relationship between health insurance plans and retail providers in low- and middle-income countries. This case study provides insights that countries can use when designing ways to include retail outlets in their health insurance schemes.